Drivers of Child Marriage among Rohingya Refugees in Malaysia - Samuri, Mohd Al Adib; Mohd Awal, Noor Aziah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Child marriage is a significant issue among refugee populations, often driven by instability, migration, and poverty. This study aims to explore the drivers of child marriage within the Rohingya refugee community in Malaysia, addressing a research gap that has primarily focused on refugees from other countries. A qualitative methodology was employed, consisting of semi-structured interviews with 20 Rohingya males and females who married before the age of 18 in Malaysia. The study found that poverty, limited access to education, and bride trafficking were the main factors leading to child marriage. Many Rohingya families viewed marriage as a way to reduce financial burdens, and bride trafficking to Malaysia for marriage was identified as a concerning practice that requires urgent intervention. The significance of this study extends beyond Malaysia, calling for both international and domestic authorities to address child marriage in refugee contexts and propose targeted interventions, such as improving access to education and dismantling bride trafficking networks.